Long-chain acyl-CoA esters in metabolism and signaling: Role of acyl-CoA binding proteins. (July 2015) - Neess, Ditte; Bek, Signe; Engelsby, Hanne; Gallego, Sandra F.; Færgeman, Nils J.
Abstract: Long-chain fatty acyl-CoA esters are key intermediates in numerous lipid metabolic pathways, and recognized as important cellular signaling molecules. The intracellular flux and regulatory properties of acyl-CoA esters have been proposed to be coordinated by acyl-CoA-binding domain containing proteins (ACBDs). The ACBDs, which comprise a highly conserved multigene family of intracellular lipid-binding proteins, are found in all eukaryotes and ubiquitously expressed in all metazoan tissues, with distinct expression patterns for individual ACBDs. The ACBDs are involved in numerous intracellular processes including fatty acid-, glycerolipid- and glycerophospholipid biosynthesis, β-oxidation, cellular differentiation and proliferation as well as in the regulation of numerous enzyme activities. Little is known about the specific roles of the ACBDs in the regulation of these processes, however, recent studies have gained further insights into their in vivo functions and provided further evidence for ACBD-specific functions in cellular signaling and lipid metabolic pathways. This review summarizes the structural and functional properties of the various ACBDs, with special emphasis on the function of ACBD1, commonly known as ACBP.